Translation of Lithuanian Adverbial Participle into English - Tekorienė, D. (Kalbotyra, 1972)
The Lithuanian Adverbial Participle can be rendered into English by four main lexico-grammatical constructions: adverbial subordinate clauses, nominal prepositional phrases. gerundial constructions and participial constructions, The use of one or another means of translation is determined by the following factors:1. The lexical and the grammatical meanings of the adverbial participle.2. The general meaning of its agent.3. The functional style of the text in which the adverbial participle occurs.